Prevalence of lymphedema after mastectomy in women living with breast cancer: a systematic review of the influence of immediate reconstruction - Rafael Vilela Eiras Ribeiro (Revista Brasileira de Cirurgia Plástica)
This study aimed to analyze, through systematic review of literature, the influence of immediate reconstruction on the prevalence of lymphedema after mastectomy, in women living with breast cancer. The analysis considered the most relevant studies originally published, in any language, up to August 2018, indexed on the databases of the US National Library of Medicine, Cochrane Central Register of Controlled Trials, Web of Science, and Scientific Electronic Library Online. The sample comprised 10 publications that met the established criteria for inclusion and exclusion , including 2,425 patients who were subjected to mastectomy alone, and 2,772 patients who were subjected to mastectomy associated with immediate reconstruction of the breast . The prevalence of lymphedema was 20.95% in patients who had been subjected to mastectomy alone (n = 508), and 5.23% among those patients who were subjected to mastectomy associated with immediate reconstruction of the breast (n = 145), the difference being statistically significant (p < 0.001). We concluded that mastectomy, when associated with immediate breast reconstruction, has a positive influence on the prognosis of patients living with breast cancer, thereby providing a much lower rate of lymphedema when compared with mastectomy alone.